Ab initio Description of Materials Properties: An Application to Thermoelectric and Raman Scattering Phenomena - Guerra-Castro, Juan Manuel; Justus Liebig University Giessen (My University, 2019)
The need of efficient and sustainable alternatives to raw materials for technological applications has driven an intense research effort in the field of materials science. The scientific strategies aim to replace or supplement conventional power production by alternative technologies like thermoelectric generators or solar cells. During my doctoral track, within the Research Training Group (RTG) 2204 "substitute materials for sustainable energy technologies", I performed theoretical - ab initio - calculations of materials properties. For that purpose, I used density functional theory (DFT) techniques to find the energy eigenvalues of the physical quantum system, and the charge density. My calculations allow me to determine the electronic parameters of thermoelectric materials, and the Raman spectral properties of graphene. For thermoelectric conversion, I studied magnesium silicide that shows enhanced thermoelectric performance when silicon is substituted by germanium or tin. Within the KKR formalism, I studied the full-relativistic effects on the electronic bands. For treating substitutional alloy systems, I used the in-site (single-cell) coherent potential approximation (CPA) to map a band structure for any intermediate composition and thereby to extract the electronic parameters. These results allow me to interpret the structural instability found in intermediate alloys, the variation of band gaps, and parabolic band effective masses with the composition. This change is nearly linear for substitutions between silicon and germanium, but non-linear terms - or deviations from Vegard´s law - appear when silicon or germanium is substituted by tin. At a particular intermediate composition, I describe the degeneracy of the conduction bands that has been shown to enhance the electronic transport properties of the n-type samples, not present in the substitution between silicon and germanium. For the interpretation of the Raman spectra in graphene samples, I compute the phonon frequencies and electronic band structures. Graphene, besides its rich physical properties, present a cheaper and more efficient alternative for carbon-based technologies. Raman spectra is a powerful method to characterize defects in these materials, i.e., boundaries, stacking, ripples, etc., through the scattering of an external light source. For non-crystalline materials, a defect-induced Raman mode, or the D-mode, is activated involving phonons away from the zone center. I compute the Raman shifts of the D mode using a resonant process that involves the intra-valley inelastic dispersion with a phonon and the elastic scattering of the defect, which explains very well the dispersion observed for different light energies. For small size samples, I describe the effect of the boundary on the Raman spectrum using a phonon-confinement model that relax the phonon conservation rules and broadens the Raman signals. In general, my calculations show a very good agreement with available experimental trends and provide intermediate data not yet reached. Therefore, these findings have served to interpret the experiments and to predict new possible results.
Keywords: ab initio; thermoelectric; Raman; DFT; ddc:530